If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(3x-6)(x+5)(x+5)=0
We multiply parentheses ..
7(+3x^2+15x-6x-30)(x+5)=0
| 5y-3=2,2y+1=5 | | 4 • 3 + 3x= 30 | | 4x-30=20-x | | y(2+y)+(2+y)-28=0 | | 9/5+3/5x=57/20+5/4x+1/4 | | 627=24b | | 3(8)-y=28 | | 7.3^(x+2)=6.x(3^(2x)-1) | | -3n+8=5 | | 7.3^(x+2)=6.x(3(2x)-1) | | y(2+y)+2+y-28=0 | | 3x/4-9=6+9 | | 24-y=28 | | 7/3+3y=6y-1/15 | | 5+3r-3=7r+20-2r | | 4(3x-5=22 | | 9x=6x+12, | | 7.3^(x+2)=6x(3^2x-1) | | 5(x+9)=17 | | |5x-1|=|6x-3| | | x+(611/10*(-5/10))=0 | | y^2+3y-30=0 | | 4-(3,5x+2)=x-7 | | 3/2=k/3 | | 70x/2+25=200 | | ¹/₄(2-x)=9 | | 1+1/2=k/3 | | 3x−9=3 | | 4x+2^x-1=0.25 | | 4,5x+3x+3=380 | | 11/2=k/3 | | 5(x^2-1)=135 |